ghrs
Answered

Get the answers you need at Westonci.ca, where our expert community is dedicated to providing you with accurate information. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

I need help ASAP please help me I’ll give Brainliest

I Need Help ASAP Please Help Me Ill Give Brainliest class=

Sagot :

irspow

Answer:

Step-by-step explanation:

A and C are equivalent.

6d+6=2(3d+3)

6d+6=3d+3+3d+3=(3d+3)+(3d+3)

Answer:

A and C

Step-by-step explanation:

Given

4d + 6 + 2d ← collect like terms

= 6d + 6

Comparing the following

A

2(3d + 3) ← distribute parenthesis by 2

= 6d + 6

B

6(d + 6) ← distribute parenthesis by 6

= 6d + 36 ≠ 6d + 6

C

(3d + 3) + (3d + 3) ← remove parenthesis

= 3d + 3 + 3d + 3 ← collect like terms

= 6d + 6

Thus A and C are equivalent to the original expression